Induction of short stature and early maturity in lentil (Lens culinaris Medik.) through mutagenesis - Laskar, Rafiul Amin; Wani, Mohammad Rafiq; Jahan, Roshan; Khan, Samiullah (Journal of Agriculture and Natural Resources, 2025)
Induced mutagenesis is a pivotal tool for enhancing the genetic diversity and achieving targeted trait selection in pulse crops. In M2 and M3 generations of lentil (Lens culinaris Medik, var. Pant L-406), this study assesses the genetic variability induced in three quantitative traits viz., days to flowering, days to maturity, and plant height. Different concentrations of sodium azide (SA: 0.01%–0.04%), hydrazine hydrate (HZ: 0.01%–0.04%), and ethylmethane sulphonate (EMS: 0.1%–0.4%) were applied to the seeds. The mean values for all the three attributes showed a significant negative change, according to the results. In the M3 generation, 0.3% EMS reduced the flowering by 5.20 days and maturity by 5.60 days, resulting in the most significant decreases in both. With a negative shift of 5.12 cm in comparison to the control, 0.03% SA was the most effective in reducing the plant height. Phenotypic coefficient of variation (PCV), genotypic coefficient of variation (GCV), broad-sense heritability (h2), and genetic advance (GA) were all consistently higher in M2 generation than in the M3 generation. For flowering in M2 generation, 0.3% EMS produced the highest h2 (60.64%). These results imply that in earlier mutant generations, selection for early maturity and decreased plant height is very successful.